Pengaruh Keteladanan Orang Tua terhadap Pembentukkan Akhlak Berkomunikasi Anak di Desa Baharu Utara Kecamatan Pulau Laut Sigam Kabupaten Kotabaru - Casriati; Rismatul Jannah (Lembaga Anotero Scientific Pekanbaru, 2025)
This study was motivated by the importance of parental role modeling in shaping children's communication skills, especially in the family environment, which is the primary center of education. The phenomenon observed in Baharu Utara Village shows that there are still children who use inappropriate words in their daily interactions, thus requiring an empirical study of the relationship between parental role modeling and the formation of children's communication skills. This study aims to describe the forms of parental role modeling, describe the condition of children's communication ethics, and analyze the influence of parental role modeling on the formation of children's communication ethics. This study uses a quantitative approach with an associative research type. The research sample consisted of 62 parents selected through simple random sampling, with data collection through observation, questionnaires, and documentation, then analyzed using SPSS version 20. The results show that parental role modeling is in the adequate category (58.3%), children's communication ethics are in the good category (62.6%), and there is a significant positive influence of parental role modeling on the formation of children's communication ethics. The conclusion of this study confirms that the better the role model displayed by parents, the better the children's communication ethics, with implications for the need to increase the role of parents as role models in ethics education.